Konflik Agama di Lingkungan SMA: Analisis dan Pendekatan Resolusi - muchlis, Abdul; Suhartini, Andewi; Basri, Hasan (EDUCATIVA, 2023)
This research explains how religious conflicts occur in high schools and how to resolve these conflicts. The background to this research is the researcher's concerns about religious conflicts that occur in wider society. This needs to be addressed together, especially by Senior High School (SMA) institutions, because high school age is an age where religious conflicts are very easy to occur but can still be resolved through religious learning activities. The type of research used in this research is library research and literature research, namely research that critically reviews the information, concepts and results found. The data used in this research is primary literature data about religious conflicts and how to resolve them. And relevant secondary data for this research. Meanwhile, the data analysis method uses descriptive analysis. Research results: Religious conflict in high schools is a complex problem, but with the right approach, we can create a harmonious school environment and encourage inclusion. Collaboration between students, teachers, parents and related parties is required to implement effective conflict resolution steps. The formulation of the problem in this research is how to analyze religious conflict in high school and what resolution approach teachers must take in dealing with religious conflict in high school. This research is very important to carry out because it aims to find out how to analyze religious conflict in high school and how to approach it. resolution that must be carried out by teachers in dealing with religious conflicts in high school. Then the results of this research discussion show that conflict can occur between students due to differences in beliefs, stereotypes or prejudice, lack of understanding, group pressure, competition and intolerance. The impact of conflict between students includes damage to student relationships, negative psychology, bullying, discrimination, and disrespect for religious celebrations.